2011
DOI: 10.2341/10-321-l
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Response and Tenascin and Fibronectin Expression After Pulp Capping in Pig Primary Teeth With Mineral Trioxide Aggregate or Calcium Hydroxide

Abstract: This study evaluated the histological response and the expression of tenascin (TN) and fibronectin (FN) after pulp capping with mineral trioxide aggregate (MTA) or calcium hydroxide (CH). Class V cavities and pulp exposure were performed in 40 primary pig teeth. The pulps were capped with either MTA or CH, and the cavities were sealed with resin-modified glass ionomer cement. CH was used as a control. Seven and 70 days posttreatment, the animals were sacrificed and teeth were prepared for histological evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 29 publications
3
16
0
6
Order By: Relevance
“…Other investigations have demonstrated improved mechanical and biological properties for MTA when compared with calcium hydroxide cements (5,6). The superior biological responses of MTA have been attributed to the higher solubilization of growth factors from dentin with MTA, although other mechanisms may also contribute to its performance.…”
Section: Novel Experimental Cements For Use On the Dentin-pulp Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigations have demonstrated improved mechanical and biological properties for MTA when compared with calcium hydroxide cements (5,6). The superior biological responses of MTA have been attributed to the higher solubilization of growth factors from dentin with MTA, although other mechanisms may also contribute to its performance.…”
Section: Novel Experimental Cements For Use On the Dentin-pulp Complexmentioning
confidence: 99%
“…Mineral trioxide aggregate (MTA) has also found wide use as a pulp-capping agent (5). Other investigations have demonstrated improved mechanical and biological properties for MTA when compared with calcium hydroxide cements (5,6).…”
Section: Novel Experimental Cements For Use On the Dentin-pulp Complexmentioning
confidence: 99%
“…, Leites et al . ). Another in vivo study conducted on dog dental pulp tissue to determine immunolocalization of fibronectin after interaction of pulp with Ca(OH) 2 ‐containing material showed that fibronectin had a strong association with microcrystals formed at the surface of the cement (Tziafas et al .…”
Section: Raised Expression Of Biomoleculesmentioning
confidence: 97%
“…Expression of fibronectin has been demonstrated in vivo in dental pulps following pulp capping with Ca(OH) 2 (Yoshiba et al 1996, Piva et al 2006, Fernandes et al 2008, Leites et al 2011. Another in vivo study conducted on dog dental pulp tissue to determine immunolocalization of fibronectin after interaction of pulp with Ca(OH) 2 -containing material showed that fibronectin had a strong association with microcrystals formed at the surface of the cement (Tziafas et al 1995b).…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…It has been proposed that glycoproteins in the extracellular matrix can stimulate the formation of reparative or reactionary dentin (Smith et al 1995;Goldberg & Smith 2004;Goldberg et al 2008). In particular, tenascin and fibronectin have been identified as high molecular weight oligomeric proteins involved in odontoblastic differentiation and odontogenesis in the presence of MTA (Thesleff et al 1995;Leites et al 2011;Zarrabi et al 2011). Both glycoproteins are expressed during dentinogenesis and may be critical elements in pulp cell migration and differentiation (Zarrabi et al 2011).…”
Section: Mode Of Action In Pulp Capping and Pulpotomymentioning
confidence: 99%